4-Phenylbutyric acid and rapamycin improved diabetic status in high fat diet/streptozotocin-induced type 2 diabetes through activation of autophagy. (4th May 2021) - Gadallah, Shaimaa H.; Ghanem, Hala M.; Abdel-Ghaffar, Amany; Metwaly, Fatma G.; Hanafy, Laila K.; Ahmed, Emad K.
Abstract: An accumulating body of evidence supports the role of autophagy in the pathophysiology of T2DM. Also, abnormal endoplasmic reticulum (ER) stress response that has been implicated as a cause of insulin resistance (IR) could also be affected by the autophagic status in β-cells. The present study was designed to investigate whether autophagy is regulated in T2DM as well as to investigate the modulatory effect of the ER stress inhibitor 4-phenylbutyric acid (4-PBA) and the autophagy inducer rapamycin (Rapa) on the autophagic and diabetic status using type 2 diabetic animal model with IR. Treatment of diabetic rats with either 4-PBA or Rapa improved significantly the states of hyperglycaemia and dyslipidaemia, increased the antioxidant capacity, reduced the levels of lipid peroxidation and ER stress and increased the autophagic flux. The obtained improvements were attributed mainly to the induction of autophagy with subsequent regulation of ER stress-oxidative activation and prevention of β-cell apoptosis.